2015
DOI: 10.1371/journal.pone.0116390
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Pathway Is Active in GBM with GLI1 mRNA Expression Showing a Single Continuous Distribution Rather than Discrete High/Low Clusters

Abstract: Hedgehog (Hh) signaling pathway is a valid therapeutic target in a wide range of malignancies. We focus here on glioblastoma multiforme (GBM), a lethal malignancy of the central nervous system (CNS). By analyzing RNA-sequencing based transcriptomics data on 149 clinical cases of TCGA-GBM database we show here a strong correlation (r = 0.7) between GLI1 and PTCH1 mRNA expression—as a hallmark of the canonical Hh-pathway activity in this malignancy. GLI1 mRNA expression varied in 3 orders of magnitude among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…Since the overexpression of Gli1 and Gli2 implicated in the activation of the Hedgehog signaling pathway, we subsequently deduced that the Hedgehog signaling pathway was activated in CC. 18 The results of our study were in line with observations by Zhang et al in that miR-129-5p was depleted as CC develops. Likewise, consistent findings of the present study and evidence reported by Chan et al in that ZIC2 and Gli1 are overexpressed in CC cell lines including Hela and C-33A.…”
Section: Discussionsupporting
confidence: 93%
“…Since the overexpression of Gli1 and Gli2 implicated in the activation of the Hedgehog signaling pathway, we subsequently deduced that the Hedgehog signaling pathway was activated in CC. 18 The results of our study were in line with observations by Zhang et al in that miR-129-5p was depleted as CC develops. Likewise, consistent findings of the present study and evidence reported by Chan et al in that ZIC2 and Gli1 are overexpressed in CC cell lines including Hela and C-33A.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, blockade of SHH signaling with the chemical inhibitor Vismodegib induced cell cycle arrest and apoptosis, and downregulated GLI1 expression in patient-derived GBM cells. 136 Several studies have suggested that SHH signaling has a suppressive effect on WNT signaling. 129,137,138 For example, it was reported that GLI1 binds to the sFRP1 promoter and increases Figure 3 Cross-talk with other signaling pathways.…”
Section: Cross-talk With Met Signaling Pathwaymentioning
confidence: 99%
“…Whether Vismodegib has clinical activity in prospective glioblastoma clinical trials remains to be tested. Retrospective data indicates that Hedgehog signaling is an active and important pathway in glioblastoma [40]. …”
Section: Clinical Development Of Agents Targeting Glioblastoma Multifmentioning
confidence: 99%